Endocrine and paracrine regulation of zebrafish spermatogenesis: the Sertoli cell perspective - Schulz, Rüdiger W.; Nobrega, Rafael Henrique [UNESP]; Morais, Roberto Daltro Vidal de Souza; Waal, Paul P. de; França, Luiz Renato de; Bogerd, Jan (Brazilian Coll Animal Reproduction, 2015)
Spermatogonial stem cells (SSCs) either self-renew or differentiate into spermatogonia that further develop into spermatozoa. Self-renewal occurs when residing in a specific micro-environment (niche) while displacement from the niche would tip the signalling balance towards differentiation. Considering the cystic type of spermatogenesis in fish, the SSC candidates are single type A undifferentiated (A(und)) spermatogonia, enveloped by mostly one niche-forming Sertoli cell. When going through a self-renewal cell cycle, the resulting new single type Aund spermatogonium would have to recruit another Sertoli cell to expand the niche space, while a differentiating germ cell cyle would result in a pair of spermatogonia that remain in contact with their cyst-forming Sertoli cells. In zebrafish, thyroid hormone stimulates the proliferation of Sertoli cells and of type Aund spermatogonia, involving Igf3, a new member of the Igf family. In cystic spermatogenesis, type Aund spermatogonia usually do not leave the niche, so that supposedly the signalling in the niche changes when switching from self-renewal to differentiation. and rzAmh inhibited differentiation of type A(und) spermatogonia as well as Fsh-stimulated steroidogenesis. Thus, for Fsh to efficiently stimulate testis functions, Amh bioactivity should be dampened. We also discovered that Fsh increased Sertoli cell Igf3 gene and protein expression; rzIgf3 stimulated spermatogonial proliferation and Fsh-stimulated spermatogenesis was significantly impaired by inhibiting Igf receptor signaling. We propose that in zebrafish, Fsh is the major regulator of testis functions and, supported by other endocrine systems (e.g. thyroid hormone), regulates Leydig cell steroidogenesis as well as Sertoli cell number and growth factor production to promote spermatogenesis.
Keywords: Follicle-stimulating hormone; Growth factors; Sertoli cells; Sex steroids; Spermatogenesis; Spermatogonial stem cells; Thyroid hormones; |Zebrafish